2017
DOI: 10.1037/cbs0000065
|View full text |Cite
|
Sign up to set email alerts
|

A French version of the Balanced Time Perspective Scale: Factor structure and relation to cognitive reappraisal.

Abstract: A frequent and equal tendency to think positively about one's past and future has been conceptualised as a balanced time perspective (TP). Such a dispositional temporal orientation has been associated with higher life satisfaction and happiness. The aim of the present study was to develop and to validate a French version of the Balanced Time Perspective Scale (BTPS; Webster, 2011), which has been specifically designed to assess the combined use of positive future and past mental representations as resources fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…First, the homogenous cultural background of our respondents reduces (intercultural) generalizability of the obtained results. We note, however, that our results are highly consistent with both Dutch (Webster et al, 2014) and French (Barsics et al, 2017) studies, both of which used larger samples (N = 512 and N = 622 respectively). Second, future studies should try to include a more balanced gender ratio as this study had a high percentage of female participants with higher levels of education.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, the homogenous cultural background of our respondents reduces (intercultural) generalizability of the obtained results. We note, however, that our results are highly consistent with both Dutch (Webster et al, 2014) and French (Barsics et al, 2017) studies, both of which used larger samples (N = 512 and N = 622 respectively). Second, future studies should try to include a more balanced gender ratio as this study had a high percentage of female participants with higher levels of education.…”
Section: Discussionsupporting
confidence: 89%
“…Using the initial scale, a BTP was positively associated with self-esteem, happiness, attributional complexity, wisdom, and mental health ( Webster, 2011 ; Webster, Bohlmeijer, & Westerhof, 2014 ; Webster & Ma, 2013 ), as well as higher delay of gratification and higher ability to imagine future scenarios ( Gӧllner, Ballhausen, Kliegel, & Forstmeier, 2018 ). Recently, scores on a French version of the scale ( Barsics, Rebetez, Rochat, D’Argembeau, & Van der Linden, 2017 ) positively correlated with emotional regulation and positive affect. Using the more recent mBTPS, Vowinckel et al (2017) found that a BTP was positively correlated with measures of flow, mindfulness, and mental health and Webster (in press ) found that a BTP was also positively associated with adaptive identity styles and flourishing.…”
mentioning
confidence: 99%
“…It has also been reported that higher BTP is associated with higher life satisfaction and general happiness (Barsics, Rebetez, Rochat, D'Argembeau, & Van der Linden, 2017;Boniwell & Zimbardo, 2004;Simons, Peeters, Janssens, Lataster, & Jacobs, 2016;Webster & Ma, 2013;Gao, 2011), extraversion (Stolarski, 2016;, positive orientation (Sobol-Kwapińska & Jankowski, 2016), satisfaction with interpersonal relations (Stolarski, Wojtkowska, & Kwiecińska, 2016), emotional intelligence (Stolarski, Bitner, & Zimbardo, 2011), and mindfulness (Selma & Sircova, 2013;Stolarski, Wojtkowska, & Kwiecińska, 2016). Moreover, higher BTP is negatively correlated with pathophysiological stress (Olivera-Figueroa, Juster, Morin-Major, Marin, & Lupien, 2015).…”
Section: Balanced Time Perspectivementioning
confidence: 95%
“…S1 Table in S1 File describes demographical data and the groups scores on the Center for Epidemiologic Studies Depression Scale (CES-D) [ 32 ], the Balanced Time Perspective Scale (BTPS) [ 33 , 34 ], the Prosocialness Scale for Adults (PSA) [ 35 ], the Self-Report Altruism Scale (SRA) [ 36 ], and the Interpersonal Reactivity Index (IRI) [ 37 , 38 ]. In order to test whether groups differed on these scores independent t -tests were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Following this task, participants played the ZPG on a computer. At the end of the ZPG, participants completed the Balanced Time Perspective Scale (BTPS) [ 33 , 34 ], the Prosocialness Scale for Adults (PSA) [ 35 ], the Self-Report Altruism Scale (SRA) [ 36 ], and the Interpersonal Reactivity Index (IRI) [ 37 , 38 ]. These questionnaires were always administered in the same order.…”
Section: Methodsmentioning
confidence: 99%